Melatonin alleviates BDE-209-induced cognitive impairment and hippocampal neuroinflammation by modulating microglia polarization via SIRT1-mediated HMGB1/TLR4/NF-κB pathway. (February 2023) - Wu, Jie; Hao, Ziwen; Wang, Ying; Yan, Dongying; Meng, Jia; Ma, Honglin
Abstract: Polybrominated diphenyl ethers (PBDEs) are persistent environmental contaminants with developmental neurotoxicity, the mechanism of which remains obscure. The present study aimed to evaluate cognitive deficits and microglia-originated neuroinflammation in the hippocampus of offspring rats exposed to BDE-209 (30 and 100 mg/kg) during perinatal period. Compared to the control, BDE-209-treated rats showed significant longer escape latency and less platform crossings in tests of Morris water maze. Besides obvious hippocampal neuron damage, increased microglial activation and pro-inflammatory markers (CD86, TNFα, and IL-1β), meanwhile, decreased anti-inflammatory molecules (CD206, IL-10, and Arg1) were induced by BDE-209. Furthermore, we investigated the neuroprotection of melatonin against BDE-209 and whether through sirtuin 1 (SIRT1). Consistent with restored SIRT1 activity, enhanced deacetylation of HMGB1 and inhibited cytoplasmic translocation of HMGB1, reduced expression of proteins involved in TLR4-NF-κB pathway and nuclear transfer of phosphorylated–NF–κB p65, and ultimately suppressed microglial activation and improved spatial memory were observed in 10 mg/kg melatonin-pretreated rats, compared with BDE-209-exposed alone. These results demonstrated that melatonin ameliorated BDE-209-caused cognitive impairment partially through shifting microglia polarization towards anti-inflammatory phenotype in a SIRT1-dependent manner, suggesting a potential mechanism for prevention. Highlights: Perinatal BDE-209 exposure triggered microglial M1 polarization in hippocampus. Melatonin alleviated neuroinflammation and cognitive deficits induced by BDE-209. Melatonin shifted BDE-209-caused microglial polarization towards M2 phenotype. SIRT1-mediated HMGB1 deacetylation and TLR4-NF-κB signaling was involved.